2004
DOI: 10.1109/tvcg.2004.30
|View full text |Cite
|
Sign up to set email alerts
|

Point-based probabilistic surfaces to show surface uncertainty

Abstract: Efficient and informative visualization of surfaces with uncertainties is an important topic with many applications in science and engineering. In these applications, the correct course of action may depend not only on the location of a boundary, but on the precision with which that location is known. Examples include environmental pollution borderline detection, oil basin edge characterization, or discrimination between cancerous and healthy tissue in medicine. This paper presents a method for producing visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 22 publications
0
77
0
Order By: Relevance
“…Edwards and Nelson (2001) found that bivariate symbols depicting data and uncertainty (size combined with either focus or colour value) yielded higher confidence (along with more accurate results) than verbal and graphical depiction of uncertainty in the legend. Grigoryan and Rheingans (2004) suggested significantly higher confidence (as well as higher accuracy and shorter response times) when a point-based representation of positional uncertainty was used, compared to colour coding. Kolbeinsson (2013) reported higher confidence for shape changes than for icon degradation that also corresponded to higher response accuracy.…”
Section: User Confidencementioning
confidence: 97%
See 3 more Smart Citations
“…Edwards and Nelson (2001) found that bivariate symbols depicting data and uncertainty (size combined with either focus or colour value) yielded higher confidence (along with more accurate results) than verbal and graphical depiction of uncertainty in the legend. Grigoryan and Rheingans (2004) suggested significantly higher confidence (as well as higher accuracy and shorter response times) when a point-based representation of positional uncertainty was used, compared to colour coding. Kolbeinsson (2013) reported higher confidence for shape changes than for icon degradation that also corresponded to higher response accuracy.…”
Section: User Confidencementioning
confidence: 97%
“…In the static 3D displays they used, these techniques outperformed intrinsic techniques such as colour mapping, transparency and aliasing (a combination of transparency and blur). In related research, Grigoryan and Rheingans (2004) found that with a spatial task in a 3D display (tell if a marker is inside of the error margin of a surface), subjects were significantly more accurate and faster when the error margin was represented by points than with pseudo-colouring of the surface. In the above mentioned study by Sanyal et al (2009) subjects performed well with two kinds of spherical glyphs (varying size and colour value) in a 2D and a 3D display.…”
Section: Intrinsic/extrinsicmentioning
confidence: 99%
See 2 more Smart Citations
“…The first prototype implements a technique presented in [5] that renders a cloud of three dimensional points at a variable distance normal to a surface. The emphasis of this prototype is to show uncertainty in the exact location of the surface.…”
Section: Point Cloudmentioning
confidence: 99%